THE APPLICATION OF THE STAD TYPE COOPERATIVE LEARNING MODEL IN GLOBAL WARMING MATERIAL TO IMPROVE STUDENT LEARNING OUTCOMES - Dary Naufal Sujarwo; Wahono Widodo (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2020)
This study aims to analyze the improvement in student learning outcomes by applying the STAD type cooperative learning model in global warming material. This type of research is “The Static Group Pretest-Posttest Design” using one experimental class and one control class. The subjects of this study consisted of 32 students of class VII-C and VII-D of Junior High School 18 Surabaya, with class VII-C as an experimental class using cooperative learning type STAD and VII-D as a control class using daily learning at school. Data collection techniques using the test method (pretest and posttest). The results of this study indicate the completeness of learning outcomes in aspects of knowledge in class VII-C by applying the STAD type cooperative learning model by 100% with an increase in student learning outcomes using the n-gain test analysis of 0.75. The high category with an increase in N-gain in class VII-C by 75% with a high category of 32 students as many as 24 students, while students in the medium category by 25% as many as 8 students and those in the low category did not exist. The conclusion is that the application of the STAD type cooperative learning model in global warming material can improve student learning outcomes.